The Polar Silk Road: A Euro-Sino economic, political and geo-strategic challenge - Marsili, M. (La Unión Europea y el principio de solidaridad, 2025)
While delivering a speech at Nazarbayev University in Astana, Kazakhstan, on September 7, 2013, the Chinese President Xi Jinping proposed an ‘economic belt along the Silk Road’ that, connecting China to Central Asia, would represent the biggest market in the world. The concept is inspired by the ancient Silk Road that witnessed hundreds of years of booming trade and cultural exchange on the Eurasian continent. Named ‘The Belt and Road initiative’ (BRI) – the BRI refers to the Silk Road Economic Belt and the 21st Century Maritime Silk Road (MSR) – this strategy intends to bring countries in the world closer than ever, that is, to shorten the distance between the People's Republic of China (PRC) and other countries, and to facilitate trade in Chinese goods. In March 2015, the Chinese government published the Vision and Actions on Jointly Building Silk Road Economic Belt and 21st Century Maritime Silk Road. In May 2017, the first Belt and Road Forum for International Cooperation was convened in Beijing. On June 20, 2017, the National Development and Reform Commission and the State Oceanic Administration released a document titled Vision for Maritime Cooperation under the Belt and Road Initiative, to synchronize development plans and promote joint actions among countries along the MSR. Finally, in his report to the 19th National Congress Communist Party of China (CPC), delivered on October 18, 2017, the general secretary of the CPC Central Committee announced that Beijing wanted to assume a global leadership role. This work aims to investigate the impact of the ‘Polar Silk Road’ (PSR), also known as the the ‘Ice Silk Road’ (ISR), framed within the MSR as part of the broader Chinese maritime geo-strategy, over the European solidarity and security.